Economics of the Military Draft - Hansen, W. Lee; Weisbrod, Burton A. (Quarterly Journal of Economics, 1967)
I. The conceptual framework, 396. — II. The model, 402. — III. Empirical application, 406. — IV. Some extensions of the analysis, 411. — V. Conclusion, 421.